Information Warfare Narratives: Yesterday and Today - G. V. Marchenko; S. Yu. Chimarov; N. A. Igoshin (Управленческое консультирование)
The article deals with the historical and legal aspects of the development of the means of informa- tion struggle in the world, changes in the activities of state and military administration bodies in the information and communication environment are traced, the issues of organizing information coun- teract to modern attempts to falsify the main events of the Great Patriotic War and the post-war stage of development of the Russian state are examined.The authors of the article demonstrate the use of narratives as ways of organizing the information space, trace and analyze examples of information confrontation between the past and the present, including, using the cases of modern armed conflicts between Russia and Georgia in South Ossetia and the military-political confrontation in eastern Ukraine, draw conclusions about the need to increase and update the content of the state information policy, taking into account new militarypolitical threats and dangers.